Screening, isolation and molecular characterization of @-amylase enzyme from basillus amyloliquefaciens umas 1002 - Husna, Hj. Mohd Noor. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This study concerned about the screening, isolating and molecular characteristic of a-amylase gene of Bacillus amyloliquefaciens UMAS 1002. This cellulolytic and amylolytic bacterium was isolated from sago pith waste grew in minimal starch and carboxymethy1cellulose media. The production of a-amylase enzyme was undertaken by microbial degradation of the media that produced clear haloes around the colonies indicated amylolytic and cellulolytic activity. These colonies were selected for molecular analysis; genomic DNA extraction, restriction endonuclease digestion, Polymerase Chain Reaction (PCR), and genomic cloning. Since there are some problems, a gene encoding extracellular a-amylase enzyme could not be cloned and sequenced.